Depletion of cutaneous macrophages and dendritic cells promotes growth of basal cell carcinoma in mice. - Simone König; Frauke Nitzki; Anja Uhmann; Kai Dittmann; Jennifer Theiss-Suennemann; Markus Herrmann; Holger M Reichardt; Reto Schwendener; Tobias Pukrop; Walter Schulz-Schaeffer; Heidi Hahn (PLoS ONE)
Basal cell carcinoma (BCC) belongs to the group of non-melanoma skin tumors and is the most common tumor in the western world. BCC arises due to mutations in the tumor suppressor gene Patched1 (Ptch). Analysis of the conditional Ptch knockout mouse model for BCC reveals that macrophages and dendritic cells (DC) of the skin play an important role in BCC growth restraining processes. This is based on the observation that a clodronate-liposome mediated depletion of these cells in the tumor-bearing skin results in significant BCC enlargement. The depletion of these cells does not modulate Ki67 or K10 expression, but is accompanied by a decrease in collagen-producing cells in the tumor stroma. Together, the data suggest that cutaneous macrophages and DC in the tumor microenvironment exert an antitumor effect on BCC.